(untitled) (Rheumatology Reports, 2011)
A lack of understanding about fibromyalgia and how to live with it may undermine the foundations of self-management and may compromise quality of life. The purpose of this study was to determine the information needs and preferences pertinent to people living with fibromyalgia. A cross-sectional web-based survey was developed based on conceptual and qualitative work informing information needs. Recruitment took place through hospitals, clinics, physicians and fibromyalgia support groups across Canada. Descriptive statistics using SPSS and graphical representations were employed to summarize and represent data. A total of 442 respondents (93% female, mode age 51-65) participated in the survey. No statistical differences in information needs were found between males and females or education level. Respondents (74%) frequently searched for information about fibromyalgia using a variety of resources including Internet (91%), doctors (75%), support groups (76%), and people with same condition (87%). Respondents expressed a strong need for information about symptoms (81%), implications (79%), treatments (87%), resources (85%) and coping (79%). However, concerns were expressed about the reliability of information and majority (93%) wanted information to be available online that is provided by healthcare providers or from reputable sources. Internet (48%), people with similar condition (35%) and support groups (35%) were perceived as useful resources for people living with fibromyalgia. Information resources need to be developed on the basis of both content and knowledge of the information needs of the target end-user. Healthcare providers and the Internet are expected to be reliable resources of information.